1975
DOI: 10.1103/revmodphys.47.637
|View full text |Cite
|
Sign up to set email alerts
|

Structural instability and superconductivity in A-15 compounds

Abstract: Structural instabilities are now being found in many high-temperature superconductors. Compounds with the A-15 (P-W) structure comprise the most important group of these materials, and their properties have been extensively studied for over 15 years. A review is given of some of these results, particularly those relating to the elastic behavior. The empirical relation of the structural instability and the anharmonicity to the high superconducting transition temperature is discussed. CONTENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
177
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(184 citation statements)
references
References 89 publications
7
177
0
Order By: Relevance
“…One of them is Nb 3 Sn, a material which similar to NbTi is in technological use, and in which the structural, electronic, magnetic, elastic, vibrational, and superconducting properties have been widely documented. [8][9][10][11] Several studies have shown that the specific heat of Nb 3 Sn does not vanish exponentially at low temperature below ϳT c / 4; these studies were generally limited to zero field or were not sufficiently detailed, so that no definitive conclusions could be drawn. In this paper, we reinvestigate the specific heat in the temperature range from 1.2 K to well over T c , in several magnetic fields up to 16 T, in order to decide if the origin of this anomaly lies in the lattice vibrations or in the electronic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is Nb 3 Sn, a material which similar to NbTi is in technological use, and in which the structural, electronic, magnetic, elastic, vibrational, and superconducting properties have been widely documented. [8][9][10][11] Several studies have shown that the specific heat of Nb 3 Sn does not vanish exponentially at low temperature below ϳT c / 4; these studies were generally limited to zero field or were not sufficiently detailed, so that no definitive conclusions could be drawn. In this paper, we reinvestigate the specific heat in the temperature range from 1.2 K to well over T c , in several magnetic fields up to 16 T, in order to decide if the origin of this anomaly lies in the lattice vibrations or in the electronic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional instabilities also exist within materials of higher dimension and can play a dominant role in determining their properties. For example, in the cubic A15 compound V 3 S, dense linear chains of V atoms provide an enhanced density of states at the Fermi surface, leading to an unexpectedly high superconducting transition temperature 7 . Similarly, Fermi surface nesting along particular directions in reciprocal space dominates the magnetic behaviour of threedimensional elemental Cr 8 and the two-dimensional, rare-earth tritellurides 9 .…”
mentioning
confidence: 99%
“…This is reminiscent of Martensitic transitions in some of the A15 compounds [23], except that here this occurs as a function of pressure at T = 0. While the underlying mechanism for superconductivity in pnictides is believed to be magnetic in origin, we conjecture that phonon mode softening, and strong magneto-elastic coupling that our calculations suggest, may be consequential to the pressure (2)), (c) elastic constants C ij (units GPa), and (d) eigenvalues λ k (units GPa) all as functions of pressure P (GPa).…”
Section: Discussionmentioning
confidence: 99%